Assessment of Volatile Chemical Composition of Essential Oil of Schinus molle (L.), Myrtus communis (L.), and Eucalyptus camaldulensis (Dehnh.) Grown in Erbil, Iraq - Safar, Ausama Abdulwahab (Iraqi Journal of Science, 2026)
The upregulation of aquaporin 3 (AQP3) channels in the cell membrane promotes malignant cell migration, proliferation, and invasive capabilities. The translation inhibition of AQP3 mRNA in the 3̍-UTR of AQP3 crucial for reducing the synthesis of AQP3 channels and preventing or lowering breast cell migrations and proliferations. Promoter markers such as hypoxia inducible factor one alpha (HIF-1α), tumor suppressor protein (p53), and estradiol (E2) are associated with the progression of breast mass disease and also induce the AQP3 expression. The aim of this study is to investigation the possible association of SNP (rs16919255) in 3̍-UTR of AQP3 gene with the intracellular levels of HIF-1α, p53, and E2. Sixty–five breast tumor tissues (0.7-1g) were collected from adult female patients aged between 18-80 years admitted at Al-Hussein Teaching hospital and AL-Haboubi Teaching Hospital. These samples were classified in two groups according to the tumor histopathological examination results, 21(32%) were malignant tissue with intensive ductal carcinoma not otherwise specified (IDC: NOS) and the other 44 (68%) were benign diagnosed as fibroadenoma. Tissue samples were washed with phosphate buffer saline for intracellular detection of HIF-1α, p53 and E2 levels using the ELISA technique, and were prepared for molecular analysis of SNP rs1691955 in the 3̍-UTR AQP3 by PCR. Intracellular levels of HIF-1α, p53 and E2 levels were elevated in patients with IDC as compared to those with fibroadenoma. The molecular analysis of AQP3 SNP (rs16919255) revealed a 33% high occurrence of rs1691955 SNP in malignant case of IDC: NOS, whereas only one case (2%) in the fibroadenoma group exhibited this variant. Additionally, there was non-significant difference in these parameters between groups having rs16919255 variant and those without this SNP. The occurrence of rs1691955 SNP in 3̍-UTR AQP3 gene didn’t associated with the levels of intracellular promoters HIF-1α, p53 and E2 hormone.